Sounds of Muziki wa Injili: Temporal and Spatial Aesthetics of Contemporary - Church Music in Dar es Salaam, Tanzania. Imani Sanga. 2010. Saarbrucken, Germany: Lap Lambert Academic Publishing. 231 pp. photos, transcriptions, ISBN 978-3-8383-6325-7. - Jorritsma, Marie (International Library of African Music, 2010)
pages: 137-138
Keywords: Church music; Aesthetics; African Music; Tanzania; Dar es Salaam; Temporal Aesthetics; Spatial Aesthetics